Trade openness and monetary policy in the Democratic Republic of Congo - Gracia Mokondi Mosunga (Cogent Social Sciences)
An open economy is conducive to the growth of international trade and enhances a nation’s global competitiveness. However, trade is frequently conducted in different currencies, which implies an exchange rate. Fluctuations in the exchange rate are likely to impact monetary policy transmission to economic growth and inflation. Consequently, trade openness can affect the effectiveness of monetary policy. Understanding this effect is essential in a dollarized economy and is dependent on the mining sector. The dollarization of the economy facilitates the amplification of exchange rate fluctuations in inflation. Mining exports depend on the international economic situation, making foreign exchange reserves vulnerable. This is likely to affect the exchange rate and, consequently, inflation. This article contributes to this fascinating but largely unexplored literature by focusing on the Congolese economy. It highlights the dollarization of the economy and the structure of trade as factors that amplify the effects of trade openness. The bayesian vector autoregression model is used for this purpose, as it is best suited when the sample size is limited. It is also inexpensive, reproducible, and accurate on average. The estimation results show that the effectiveness of monetary policy on inflation and economic growth is reduced as trade openness increases.